An assessment of DSS design science using the Hevner, March, Park, and Ram guidelines. - Arnott, David; Pervan, Graham (Australian National University ANU, 2008)
Design science has been an important strategy in decision support systems (DSS) research since the inception of the field in the early 1970s. Recent reviews of DSS research have indicated a need to improve its quality and relevance. DSS design science has an important role in this improvement as design science can engage industry and the profession in intellectually important projects. The 2004 publication of the Hevner, March, Park, and Ram (HMPR) Guidelines for the conduct and assessment of information systems design science provides a vehicle for assessing DSS design science. This paper presents research that used bibliometric content analysis to apply the HMPR Guidelines to a representative sample of DSS design-science papers in 14 journals. The analysis highlights issues that need attention, notably, evaluation, research design, and theorizing. Comments are also offered on the experience of applying the HMPR Guidelines to a large body of research.